2022
DOI: 10.3390/vaccines10020194
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Inequities in COVID-19 Vaccine Roll-Out Strategy Programs: A Cross-Country Study Using a Machine Learning Approach

Abstract: After the start of the COVID-19 pandemic and its spread across the world, countries have adopted containment measures to stop its transmission, limit fatalities, and relieve hospitals from straining and overwhelming conditions imposed by the virus. Many countries implemented social distancing and lockdown strategies that negatively impacted their economies and the psychological wellbeing of their citizens, even though they contributed to saving lives. Recently approved and available, COVID-19 vaccines can prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Another top feature that significantly predicts COVID-19 vaccination uptake is Gross Domestic Product (GDP). This finding is in line with [115][116][117]. The association between GDP and higher vaccination rate is, however, intuitive.…”
Section: Global Feature Importancesupporting
confidence: 85%
See 3 more Smart Citations
“…Another top feature that significantly predicts COVID-19 vaccination uptake is Gross Domestic Product (GDP). This finding is in line with [115][116][117]. The association between GDP and higher vaccination rate is, however, intuitive.…”
Section: Global Feature Importancesupporting
confidence: 85%
“…As Roghani and Panahi [116] have a notably higher GDP, this can contribute to the higher vaccination rate due to the fact that GDP, national strategy, and proper utilization of the resources of a country are likely to be highly associated. A study conducted by Kazemi et al [117] also found evidence of the association between median per capita income and overall vaccination adoption. The authors used the Random Forest algorithm for their analysis on a data set of 142 countries.…”
Section: Global Feature Importancementioning
confidence: 89%
See 2 more Smart Citations
“…their spouse. Accessing the internet has been well explored as a barrier to COVID-19 vaccination, [ 5 , 19 ] and future efforts will require healthcare systems to provide alternate access points for vaccine registration. While initially a limitation, the recent passage of the SAVE LIVES Act [ 20 ] now allows for vaccination of Veterans’ caregivers and family members and has tasked the VA with expanding eligibility from 9 million to more than 33 million individuals in the United States [ 21 ].…”
Section: Discussionmentioning
confidence: 99%